Bilateral proximal ureteral and ureterovesical junction obstruction in a child - Daniel A. Reich; Christopher E. Bayne; Cynthia A. Sharadin; Romano T. DeMarco (Urology Case Reports, 2023)
The most common sites of ureteral obstruction in children are at the level of the ureteropelvic junction (UPJ) and ureterovesical junction (UVJ). Bilateral hydronephrosis or hydroureteronephrosis due to varying degrees of obstruction at the UPJ or UVJ is common in children and typically improves with time. Clinically significant obstruction at both locations in an ipsilateral ureter occurs less commonly and rarely requires both dismembered pyeloplasty and ureteral reimplantation. We believe this case report is the first description of bilateral proximal and distal ureteral obstruction requiring both dismembered pyeloplasty and ureteral reimplantation.